Benjamin W. Betts and his computable approach towards morphogenesis. (March 2023) - Soltan Rahmati, Hossein; Ayatollahi, Mohammad Hossein
Morphological theories in architecture are more popular than ever partly due to the rapid developments in computational techniques. This rapid development, however, is more fruitful when it is informed of the philosophical and ethical bases of such techniques. The neglected historical case of Benjamin W. Betts, an architect of the late Victorian Britain, is an early example of the effects of philosophical presuppositions on computable theories of morphogenesis in arts and architecture. The aims of this study are to shed light on his motivations and sources of inspiration, and also to present an algorithm for his procedure. We used the only book available on the Betts' works in addition to archival materials to conduct the research. Betts was under heavy influence of Idealism and Oriental thought in his symbology and the morphogenetic procedure he designed. The Python/Grasshopper algorithm for Rhino presented in this paper produces two dimensional Betts' diagrams that can be used as an educational tool or an opportunity of enjoying the beauty of mathematical forms, and the immense variety they offer thanks to parameterization.